2011
DOI: 10.1002/qj.963
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐site evaluation of an urban land‐surface model: intra‐urban heterogeneity, seasonality and parameter complexity requirements

Abstract: Citation: Loridan T, Grimmond CSB. 2012. Multi-site evaluation of an urban land-surface model: intra-urban heterogeneity, seasonality and parameter complexity requirements. Q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 44 publications
(58 reference statements)
3
55
0
Order By: Relevance
“…In other work, Loridan et al (2010) evaluated the single-layer urban climate model (SLUCM), as a component of the mesoscale Weather Forecasting Model (WRF) model, and found that data on vegetative cover was especially important for improved simulations. Similarly, Loridan and Grimmond (2012) using the same model found that using data that described the character of urban neighbourhoods where flux observations are made, rather than using generic urban data, had a marked effect; SLUCM was better able to reproduce the turbulent fluxes at 15 sites across the US, Mexico, Canada, Australia, Finland and Poland.…”
Section: Urban Energy Budget (Ueb) Modelsmentioning
confidence: 87%
“…In other work, Loridan et al (2010) evaluated the single-layer urban climate model (SLUCM), as a component of the mesoscale Weather Forecasting Model (WRF) model, and found that data on vegetative cover was especially important for improved simulations. Similarly, Loridan and Grimmond (2012) using the same model found that using data that described the character of urban neighbourhoods where flux observations are made, rather than using generic urban data, had a marked effect; SLUCM was better able to reproduce the turbulent fluxes at 15 sites across the US, Mexico, Canada, Australia, Finland and Poland.…”
Section: Urban Energy Budget (Ueb) Modelsmentioning
confidence: 87%
“…The inaccuracies have been well documented (Best and Grimmond, 2015) and there have been studies done that have utilized parameterization techniques and different model schemes to try and get better agreement between the model and the observations (e.g. Loridan and Grimmond, 2012;Loridan et al, 2010). Loridan and Grimmond (2012) conducted a study using an offline Noah/SLUCM model to assess errors across 27 observational datasets, which represented 15 different urban sites at different times of the year.…”
Section: Pbl and Lsm Scheme Sensitivity And Improving Simulations Ovementioning
confidence: 99%
“…Loridan and Grimmond, 2012;Loridan et al, 2010). Loridan and Grimmond (2012) conducted a study using an offline Noah/SLUCM model to assess errors across 27 observational datasets, which represented 15 different urban sites at different times of the year. In addition, five sets of parameter values and parameter configurations were used to try to reduce the errors across the 27 datasets.…”
Section: Pbl and Lsm Scheme Sensitivity And Improving Simulations Ovementioning
confidence: 99%
“…Geometric and thermal parameters for the UCM have a significant effect on the transfer of energy and momentum between the urban surface and the atmosphere Wang et al 2011;Loridan and Grimmond 2012). The parameters used in this study are summarized in Table 1; most parameters are based on Kusaka et al (2001).…”
Section: Urban Surface Modelsmentioning
confidence: 99%